MANAJEMEN STRATEGIS DALAM MEWUJUDKAN SEKOLAH PEDULI DAN BERBUDAYA LINGKUNGAN - Soleh, Badrus; Astri Norisa Irfandari; Kacung Wahyudi; Hilmi Qosim Mubah (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2025)
This study aims to analyze strategic management in creating an environmentally conscious and cultured school at SMPN 2 Larangan. With a descriptive qualitative approach, we collected data through interview, observation, and documentation methods. Data sources consisted of the principal, teachers, educators, and students. To analyze the data, this study used the Miles and Huberman model which involved three stages: data condensation, data presentation, and drawing conclusions. The findings of this study indicate that SMPN 2 Larangan has implemented environmental strategic management through three main steps, namely: strategy formulation, implementation, and evaluation. The strategy formulation process is carried out by integrating environmental aspects into the school's vision, mission, and curriculum. The formation of the Adiwiyata team involving 16 working groups (Pokja) and 76 students as environmental cadres is the key to the strategy. The implementation of the program includes various innovative initiatives such as water and energy conservation, waste management, plant maintenance, and development of environmentally based products. The school has also revamped the Learning Implementation Plan (RPP) so that each subject can educate students about the importance of protecting the environment. A participatory approach involving all stakeholders is a very important success factor. Strategy evaluation is carried out periodically every three months by a special team, with success indicators that are not only seen from an administrative perspective, but also from a real impact on environmental and behavioral changes. The peak of success is marked by the achievement of the Adiwiyata Mandiri predicate and recognition as a plastic waste-free zone.